Perang Dunia II: Strategi Perang Darat Jepang - Bachri, Daffaraihan Adam; Hasan, Said Hamid; Mulyana, Agus (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
The Success of Japanese military operations in World War II, other than modern armaments, was also supported by effective war strategies and tactics to reach a victory. Japan’s victory over the Allies, which led to the fall of Southeast Asia to the hand of the Japanese in the first phase of World War II, and the heavy losses suffered by the Allies at the end of World War II, proves that victory in war cannot be achieved only by armament modernization, but must be accompanied with the effective war strategies and tactics and an ability to adapt in the battlefield. The purpose of this research is to find out about ground warfare strategies used by the Japanese in military operations in Southeast Asia and the Pacific Islands in World War II. The research method used the historical method. This study is a development of previous studies that discuss Japan’s war strategy in World War II. However, this study focuses more on the ground warfare strategies and tactics used by the Japanese Army, their implementation on the battlefields in Southeast Asia and the Pacific Islands, and their impact on the Allies in World War II.